The Proposed Culturally Rich Instructional Materials of Integrated Oral Course for The Fifth Semester Students of D3 English Program at University of Merdeka Malang - Farani, Yasmin (EnJourMe (English Journal of Merdeka) : Culture, Language, and Teaching of English, 2016)
This article is based on an Educational Research and Development (R D) which was conducted in order to develop materials for teaching integrated skills (listening and speaking) to the fifth semester students of D3 English Program at University of Merdeka Malang. The materials themselves were intended to be used to teach and learn not only skills but American culture as well. As the human instrument, the researcher was helped by secondary instruments such as questionnaires, checklist and observation. To develop the materials, two essential steps proposed by Graves (1996) and material evaluation and selection step proposed by Cunningsworth (1995) were thoroughly applied in the research.